The costs of agglomeration: Land prices in French cities - Pierre-Philippe Combes; Gilles Duranton; Laurent Gobillon (Institute for the Study of Labor (IZA), 2012)
We develop a new methodology to estimate the elasticity of urban costs with respect to city population using French land price data. Our preferred estimate, which handles a number of estimation concerns, stands at 0.041. Our approach also yields a number of intermediate outputs of independent interest such as a distance gradient for land prices and the elasticity of unit land prices with respect to city population. For the latter, our preferred estimate is 0.72.
Keywords: R14; R21; R31; 330; urban costs; land prices; land use; agglomeration; Bodenpreis; Städtischer Immobilienmarkt; Agglomerationseffekt; Kosten; Frankreich